European Veterinary Renal Pathology Service: A Survey Over a 7‐Year Period (2008–2015). (1st August 2017) - Aresu, L.; Martini, V.; Benali, S.L.; Brovida, C.; Cianciolo, R.E.; Dalla Riva, R.; Trez, D.; Van Der Lugt, J.J.; Van Dongen, A.; Zini, E.
Abstract : Background: The European Veterinary Renal Pathology Service (EVRPS) is the first Web‐based registry for canine renal biopsy specimens in Europe. Hypothesis/Objectives: The aim was to verify whether differences exist between the clinical and laboratory presentation of dogs with nephropathy according to renal pathological findings, as defined by light and electron microscopy of renal biopsy specimens submitted to EVRPS. Animals: Renal biopsy specimens of dogs were collected from the archive of the service (n = 254). Cases were included if both light and electron microscopy were available (n = 162). Methods: Renal biopsy specimens were classified based on the morphological diagnoses. Thereafter, they were grouped into 3 disease categories, including immune‐complex‐mediated glomerulonephritis (ICGN), non‐immune‐complex‐mediated GN (non‐ICGN), and renal lesions not otherwise specified (RL‐NOS). Differences among morphological diagnoses and among disease categories were investigated for clinical and laboratory variables. Results: Serum albumin concentration was lower in dogs with ICGN than in those with non‐ICGN ( P  = 0.006) or RL‐NOS ( P  = 0.000), and the urine protein‐to‐creatinine ratio (UPC) was significantly higher in ICGN than in the other 2 disease categories. Regarding morphological diagnoses, albumin was significantly lower in amyloidosis (AMY) and membranous (MGN), membranoproliferative (MPGN) or mixed glomerulonephritis (MixGN) than in minimal change disease, primary (FSGS I) or secondary (FSGS II) focal and segmental glomerulosclerosis and juvenile nephropathies (JN). The UPC was higher in MPGN than in FSGS I and FSGS II. Conclusions and clinical importance: Dogs with ICGN, in particular MPGN, had higher protein loss than those with non‐ICGN or RL‐NOS, leading to more severe hypoalbuminemia. Clinical and laboratory differentiation among dogs with the different morphological diagnoses and among dogs with different disease categories was difficult due to overlapping results.